Evaluation of strain and stress states in the single point incremental forming process. Issue 1 (July 2016) - Neto, D.; Martins, J.; Oliveira, M.; Menezes, L.; Alves, J.
Abstract Single point incremental forming (SPIF) is a promising manufacturing process suitable for small batch production. Furthermore, the material formability is enhanced in comparison with the conventional sheet metal forming processes, resulting from the small plastic zone and the incremental nature. Nevertheless, the further development of the SPIF process requires the full understanding of the material deformation mechanism, which is of great importance for the effective process optimization. In this study, a comprehensive finite element model has been developed to analyse the state of strain and stress in the vicinity of the contact area, where the plastic deformation increases by means of the forming tool action. The numerical model is firstly validated with experimental results from a simple truncated cone of AA7075-O aluminium alloy, namely, the forming force evolution, the final thickness and the plastic strain distributions. In order to evaluate accurately the through-thickness gradients, the blank is modelled with solid finite elements. The small contact area between the forming tool and the sheet produces a negative mean stress under the tool, postponing the ductile fracture occurrence. On the other hand, the residual stresses in both circumferential and meridional directions are positive in the inner skin of the cone and negative in the outer skin. They arise predominantly along the circumferential direction due to the geometrical restrictions in this direction.